Anticoagulant Complications in Coronavirus Disease (Covid-19) Patients: Literature Review - Afifah, Siti Zulfatul; Sulistyani, S (Prosiding University Research Colloquium, 2022)
The most common thrombotic complication in severe COVID-19 patients is venous thromboembolism, following the events of venous and arterial thrombosis are deep vein thrombosis, pulmonary embolism, ischemic stroke, myocardial infarction, and systemic arterial embolism. Patients with COVID-19 often have a thrombosis incidence of 31%. Anticoagulation is a therapy to treat thrombosis as a complication of COVID-19. Administration of anticoagulants causes several complications, including bleeding that can cause death. Objective: to determine the complications of anticoagulation in patients with coronavirus disease (COVID-19). Methods: This research was written as a variety of literature with a narrative database analysis method which includes Google Scholar, Pubmed, Research Gate. Results: At the article collection stage, 1,586 titles were obtained from 3 search engines. After screening, the authors found 20 articles discussing anticoagulant complications in patients with coronavirus disease (covid-19). From the data obtained, it can be concluded that most studies show that the use of anticoagulants in COVID-19 patients has minor, major bleeding to death.